18O/16O ratios in anhydrous spinel lherzolite xenoliths from the Shavaryn-Tsaram volcano, Mongolia - Kovalenko V.I.; Harmon R.S.; Kempton P.D.; Stosch H.G.; Hoefs J.; Eonov D. (My University, 1987)
Anhydrous spinel lherzolite xenoliths from the Shavaryn-Tsaram volcano, which represent unusually clinopyroxenerich samples of upper mantle beneath the Tariat Depression in north-central Mongolia, have particularly low δ18O values of +4.9 to +5.7‰ SMOW. Constituent minerals exhibit small (ca. 0.5–0.7‰) variations in18O content (olivine = +4.6 to +5.3‰, clinopyroxene = +5.6 to +6.1‰, orthopyroxene = +5.8 to +6.5‰), that are unrelated to xenolith modal mineralogy, chemical composition, radiogenic isotope character, or pyroxene equilibration temperature. This O-isotope character of the Tariat xenoliths is interpreted to reflect the closed-system distribution of oxygen isotopes in a slowly cooling mantle diapir emplaced into the lithosphere from a relatively primitive region of the asthenosphere.